For Auld Lang Syne’: A Tale of Two Songs - Miguel Alarcão (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
ABSTRACT: Besides the Royal Family and the touristic, artistic, aesthetic, and literary fruition and appraisal of Scotland and her landscapes since the mid-18th century, two distinguished English artists have paid a musical tribute to Britain’s northernmost nation, offering us two “lyrical ballads” which, in a joint framework of the heritage and culture industries and the new memory studies, can be subject to some brief comments: Paul McCartney’s Mull of Kintyre (1977) and Rod Stewart’s Every Beat of my Heart (1986).